Implementing a survey for patients to provide safety experience feedback following a care transition: a feasibility study - Jason Scott; Emily Heavey; Justin Waring; Aoife De Brún; Pamela Dawson (BMC, 2019)
Abstract Background The aim was to determine the feasibility of implementing a patient safety survey which measures patients' experiences of their own safety relating to a care transition. This included limited-efficacy testing, determining acceptability (to patients and staff), and investigating integration with existing systems and practices from the staff perspective. Methods Mixed methods study in 16 wards across four hospitals, from two English NHS Trusts and four clinical areas; cardiology, care of older people, orthopaedics, stroke. Limited-efficacy testing of a previously validated survey was conducted through collection of patient reports of safety experiences, and thematic comparison with staff safety incident reports. Patient acceptability was determined through analysis of survey response rates and semi-structured interviews. Staff acceptability and integration were investigated through analysis of survey distribution rates, semi-structured interviews and focus groups. Results Patients returned 366 valid surveys (16.4% response rate) from 2824 distributed surveys (25.1% distribution rate). Older age was a contributing factor to lower responses. Delays were the largest safety concern for patients. Staff incident report themes included five not present in the safety survey data (documentation, pressure ulcers, devices or equipment, staffing shortages, and patient actions). Patient interviews (n = 28) identified that providing feedback was acceptable, subject to certain conditions being met; cognitive-cultural (patient understanding and prioritisation of safety), structural-procedural (opportunities, means and ease of providing feedback without fear of reprisals), and learning and change (closure of the feedback loop). Staff (n = 21) valued patient feedback but barriers to collecting and using the feedback included resource limitations, staff turnover and reluctance to over-burden patients. Conclusions Patients can provide meaningful feedback on their experiences and perceptions of safety in the context of care transitions. Providing this feedback was acceptable to some patients, subject to certain conditions being met. Safety experience feedback from patients was also acceptable to staff; quantitative data was perceived as useful to identify potential risks, and qualitative data informed types of changes required to improve care. However, patient feedback was not integrated into any quality improvement initiatives, suggesting there are still significant challenges to healthcare teams or organisations utilising patient feedback, particularly in relation to care transitions.